EVALUATION OF ANADOLU AGENCY INFOGRAPHIC APPLICATIONS BY SOCIETY FOR NEWS DESIGN - AKCA, Fadim; ÇELİK YILMAZ , Nazik (SSD Journal, 2023)
Infographics, an effective way of conveying information, use the foundation of graphic design to organize data on a specific topic, thus easily capturing the reader's attention. With the advancement of technology, the sharing of information has increased in conjunction with visual communication networks, emphasizing the importance of presenting this information accurately and aesthetically. In this research, some of the infographics related to economics and finance, culture, and arts published by the Anadolu Agency, a significant news network in Turkey, in April and May of 2016 were selected for evaluation based on the criteria of the Society For News Design (SND), an international organization. Scales were developed to assess their compatibility in terms of visual appeal and content based on SND content editing and visual design criteria. The KMO values for the SND content editing criteria scale were 0.925, and for the SND visual design criteria scale, it was 0.858. The Bartlett test results were 577.459 and 800.686 (P<0.01), respectively. The analyses showed that the scales had high internal consistency and reliability. Evaluation was carried out using these two scales, and a general survey model was used in accordance with the quantitative research paradigm. The compatibility of infographic visuals with SND criteria in terms of design and content editing was assessed. This study was conducted to emphasize the importance of designing data accurately and effectively using infographics prepared by benefiting from different disciplines and to examine the harmony and balance between visual and informational elements. The results of the research indicated that while there were "partial issues" in terms of compliance with the visual design and content editing criteria, participants expressed the opinion that the Anadolu Agency infographics were "sufficient" in terms of compliance with the visual design and content editing criteria.